The Chemistry Reading Activity in Metacognitive Knowledge - Sawuwu, Benny Yodi (SEAQIS Journal of Science Education, 2022)
An exploration of chemical reading performances of fifteen chemistry teacher candidates was conducted to reveal qualitatively metacognitive knowledge during chemistry reading activities. A think-aloud protocol had been carried out for reading performance. For a question posing purpose, two articles were designed to stimulate the readers’ thought in a metacognitive level that was divulged in-depth by self-interviewing questions. The reading performance was Tran scripted by measuring the normal reading rate and think-aloud reading rate to reveal the pattern of chemical reading activities. A phenomenological reduction method was used to analyze and to describe the reading performance. The interrelationship among declarative knowledge on reading preparation, procedural knowledge in reading performance, conditional-situational knowledge on maintaining the reading activity, and conditional-strategic knowledge on the termination of the chemical reading activity was constructed by the self-organization, task comprehension, strategy, and knowledge to integrated all sources. The presence of chemical equations, chemical representations, and terminology on the chemical reading had influenced the chemical reading pattern